The Effect of Administering Lemon Basil (Ocimum sanctum) Leaves on FSH and LH Estrogen Levels and Size of Ovarian Antral Follicle in Female Balb/C Mice - Sri Maryanti (Universitas Sultan Agung Semarang, 2020)
INTRODUCTION: Ocimum sanctum have been proven effective in decreasing Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH) levels, and sperm number, and also increase male testosterone levels. However, so far no evidence has been found on the effect of Ocimum sanctum leaves on the levels of estrogen, FSH, LH, and the size of ovarian anthral follicles. OBJECTIVES: To evaluate the effect of Ocimum sanctum leaves on estrogen, FSH, LH and the size of antral follicle of female Balb/C mice.